Garbled speech: a rare presentation of metronidazole-induced neurotoxicity. Issue 3 (1st March 2019) - Cheema, Muhammad Arslan; Salman, FNU; Ullah, Waqas; Zain, Muhammad Abdullah
Abstract : Neurotoxicity is a rare but significant side effect of metronidazole. We present, here, a case of a 34-year-old man, presenting with garbled speech and word finding difficulty. He was taking metronidazole for the last 3 months for stage 4 decubitus ulcers. MRI of the brain showed abnormal signal intensities in the splenium of the corpus callosum and dentate nuclei of the cerebellum. The diagnosis of metronidazole-induced neurotoxicity was made based on MRI findings. The antibiotic was stopped leading to resolution of abnormal MRI findings. We advocate that metronidazole can be associated with severe neurotoxicity, but its prompt cessation leads to better outcome and prognosis.